2011
DOI: 10.1088/1741-2560/8/5/056012
|View full text |Cite
|
Sign up to set email alerts
|

Floating light-activated microelectrical stimulators tested in the rat spinal cord

Abstract: Microelectrodes of neural stimulation utilize fine wires for electrical connections to driving electronics. Breakage of these wires and the neural tissue response due to their tethering forces are major problems encountered with long term implantation of microelectrodes. The lifetime of an implant for neural stimulation can be substantially improved if the wire interconnects are eliminated. Thus, we proposed a floating light-activated micro electrical stimulator (FLAMES) for wireless neural stimulation. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 40 publications
(51 reference statements)
1
42
0
Order By: Relevance
“…2 The main objective of this study was to estimate the light energy that will be collected by the optical microstimulators at various depths of implantation inside the neural tissue. The dark regions in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The main objective of this study was to estimate the light energy that will be collected by the optical microstimulators at various depths of implantation inside the neural tissue. The dark regions in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Microelectrode implants often fail either due to the chronic tissue response caused by the tethering forces of the wires or their breakage. 4,5 A wireless neural stimulator can solve the problems associated with wire interconnects.…”
Section: Introductionmentioning
confidence: 99%
“…As a comparison, this optical power is about two orders of magnitude higher than the energy levels required to wirelessly activate neural tissue via photodiodebased floating devices implanted into the rat cervical spinal cord. 6 Nonetheless, the thermal effects should be tested for each specific application since the temperature map depends on many parameters such as the thermal properties of the tissue and the surrounding structures, the optical properties of the CNS region, and the laser beam size and shape.…”
Section: Discussionmentioning
confidence: 99%
“…6 This suggests that our microstimulators can be implanted deeper in neural tissue without exceeding the temperature limitation on the surface. In a simulation study, the maximum power for the same temperature increase was found as 325 and 250 mW∕cm 2 for the human gray and white matters, respectively.…”
Section: Maximum Allowable Optical Powermentioning
confidence: 93%
See 1 more Smart Citation